Characterizing tailings professional labor demand - Spencer, Louise, author; Scalia, Joseph, IV, advisor; Bareither, Christopher, advisor; Sanford, William, committee member (Colorado State University. Libraries, 2021)
A low-carbon future necessitates increased extraction of critical minerals via mining. The act of mining includes not only extraction of commodities, but also management of tremendous volumes of waste. Despite the need for mining to support green technologies, mining is experiencing a credibility crisis due to historic legacies of environmental damage and recent catastrophic failures of tailings (mine waste) facilities. To regain social trust and environmental credibility, the mining industry must do better at managing tailings. The recently issued Global Industry Standard on Tailings Management (GISTM) places significant demand on tailings professionals worldwide. Given these pressures, this study addresses the question: is the current tailings professional labor pool sufficient to provide the specialized labor needed to meet new guidance designed to make tailings facilities safer, and if not, how can this shortage be rectified? To address this question, a coupled qualitative-quantitative approach was undertaken. Research was conducted to characterize the current (Spring 2021) industry practitioner perspectives on the state of tailings labor resources. Then, future tailings labor demand under the GISTM was calculated quantitatively by estimating professional labor demand based on guidelines presented in the GSITM and applied to the estimated number of tailings facilities worldwide. Finally, opportunities to address current and future tailings labor demand were identified through tailing practitioner perspectives. According to current practitioners, there is shortage of qualified tailings professionals, related to increased labor needs, difficulties of recruitment into and retention within the industry, as well as senior-level professionals retiring. Managing the minimum estimated 16,000 tailings facilities worldwide was estimated to require as many as 17,800 full-time equivalent, qualified and trained personnel. Finally, current actions to train future tailings professionals are provided, as well as recommendations for actions via collaboration between academia, industry, consultants, regulators, and non-governmental organizations (NGOs) to fortify tailings recruitment activities, training programs, and educational opportunities.
Keywords: mine dams; tailing; labor resource; tailings; mining